MANAJEMEN STRATEGIK PEMASARAN PENDIDIKAN BERBASIS MEDIA SOSIAL DI MADRASAH ALIYAH YAYASAN PONDOK PESANTREN BABAKAN JAMANIS PARIGI PANGANDARAN - Neneng Nurmalasari; Imas Masitoh (re-JIEM (Research Journal of Islamic Education Management), 2020)
This study describes an overview of the use of social media as a management marketing strategy at Madrasah Aliyah Yayasan Pondok Pesantren Babakan Jamanis. The benefits of social media as a marketing tool in the world of education in the era of the 4.0 industrial revolution are the right choice because it is increasingly accessible to various groups. This research is qualitative research with data collection methods through observation, in-depth interviews, and documentation. The results show that the social media-based educational marketing strategy management is used, namely: Facebook, Instagram, and Youtube by first identifying in the community which then becomes an educational marketing strategy by highlighting the achievements of these institutions. The management of private education, supported by stakeholders and adequate facilities has provided a distinctive feature and strength in the management of educational marketing strategies at Madrasah Aliyah Yayasan Pondok Pesantren Babakan Jamanis.